Factor Structure of the Fourth Edition of the Millon Clinical Multiaxial Inventory - Bazmara, Davoud; Kamkari, Kambiz; Salehi, Mahdieh; Mardani Rad, Mojgan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The aim of the present study was to examine the construct validity (factorial) of the fourth edition of the Millon Clinical Multiaxial Inventory (MCMI-IV) with an emphasis on personality patterns and personality disorders.Methods and Materials: Given the nature of standardization, this study employed an analytical cross-sectional method. This method examined the current status and situation and included both descriptive and correlational methods. The statistical population of this study comprised all individuals who visited counseling centers or treatment clinics in Tehran from June 2022 to September 2022. Participants were at least 18 years old, had completed at least five grades of schooling, and had either sought initial treatment or continued their treatment at these centers or had been referred to them. In this study, a purposive sampling method was used to select 500 visitors from counseling centers in Tehran. The measurement tool included the standardized Millon Clinical Multiaxial Inventory (fourth edition). To analyze the data statistically, the KMO index, Bartlett's test, and factor analysis were performed using SPSS-26 software.Findings: The results of the factor analysis in this study of visitors to family counseling centers in Tehran indicated that four factors were identified: 1) styles of clinical personality patterns, 2) severe personality pathology, 3) clinical syndromes, and 4) severe clinical syndromes.Conclusion: These results demonstrate that the MCMI-IV has a distinct factor structure that can effectively measure personality and clinical characteristics. This factor analysis enhances the construct validity of the test and improves the accuracy of measuring the intended characteristics. Based on the findings of the present study, it can be concluded that the fourth edition of the MCMI has a suitable factor structure and can be used as a reliable tool for measuring personality and clinical characteristics. These findings can aid researchers, counselors, and physicians in diagnosing and treating personality and clinical disorders.